Costs, Benefits and the Political Economy of Aid Coordination: The Case of the European Union. Issue 1 (January 2017) - Klingebiel, Stephan; Negre, Mario; Morazán, Pedro
Abstract Although it is not possible to identify a specific, theoretical optimum level of aid coordination for the European Union, there is a broad consensus on the need for reduced transaction costs and greater impact through a stronger adherence to coordination standards. However, neither member states nor European institutions consequently follow a policy in line with a clear coordination principle. And nor do partner countries always push for more donor coordination. This article uses evidence from two country case studies, Myanmar and Rwanda, in which a conducive aid coordination environment is assumed. The former represents the new foundation of an aid architecture in a country, thus expecting the application of high aid effectiveness standards. The latter consists of a partner government with a strong leading role in aid. Although the political economy of donors and partner countries does not always favour coordination, strong recipient government leadership is crucial to align developmental objectives and clearly establish comparative advantages and division of labour among donors. Abstract Même si ce n'est pas possible d'identifier un niveau de coordination d'aide qui soit spécifique et théoriquement optimal pour l'Union Européenne, on est d'accord sur la nécessité de réduire les couts de transaction, et sur la nécessité d'augmenter l'impact de l'aide à travers une adhérence plus forte aux standards de coordination. Cependant, soit les Etats membres que les institutions Européennes ne suivent pas une politique conforme aux principes de la coordination. Les pays partenaires non plus ne demandent pas toujours plus de coordination entre donneurs. Cet article utilise l'évidence de deux pays, le Myanmar et le Rwanda, ou on suppose que l'aide est dispensée dans un environnement de coordination. Au Myanmar, il y a une nouvelle architecture de l'aide, au sein de laquelle on supposerait que l'efficacité de l'aide dispensée est gouvernée par des standards très hauts. Au Rwanda, le gouvernement prend un rôle de premier plan dans la coordination de l'aide. Même si la politique économique des pays donneurs et récipiendaires n'est pas toujours coordonnés, c'est impératif d'avoir une direction forte chez les récipiendaires, ce qui aide l'alignement des objectifs et la division du travail parmi les donneurs en base à leurs avantages comparatifs.